2021
DOI: 10.1007/s43615-021-00132-y
|View full text |Cite
|
Sign up to set email alerts
|

New Kids on the Recycling Block: the Role of Supermarkets and Bodegas for Sustainable Consumer Behaviour in Lima

Abstract: Only 4% of total municipal solid waste in Lima is recycled. Supermarkets and bodegas are in a unique, highly relevant position for the transition towards a circular economy due to their direct influence on customers’ consumption patterns. This paper explores the role of supermarkets and bodegas for consumer recycling behaviour, looking both at already implemented practices and possibilities for the future. Based on semi-structured interviews conducted with key actors in the recycling sector in 2019 and 2020, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The circular economy's use in the process contributes to the chain's sustainability and ensures less environmental impact [18]. Borasino and Fuhrmann-Riebel [19] found that national and international pressure on superstores to adopt sustainability actions can be a competitive advantage and a good economic reason to advocate circularity.…”
Section: Introductionmentioning
confidence: 99%
“…The circular economy's use in the process contributes to the chain's sustainability and ensures less environmental impact [18]. Borasino and Fuhrmann-Riebel [19] found that national and international pressure on superstores to adopt sustainability actions can be a competitive advantage and a good economic reason to advocate circularity.…”
Section: Introductionmentioning
confidence: 99%